2021
DOI: 10.1007/s11069-021-04533-y
|View full text |Cite
|
Sign up to set email alerts
|

A tsunamigenic delta collapse and its associated tsunami deposits in and around Lake Sils, Switzerland

Abstract: Large lacustrine mass movements and delta collapses are increasingly being considered as potential tsunamigenic sources and therefore hazardous for the population and infrastructure along lakeshores. Although historical reports document tsunami events in several lakes in Switzerland, and although the propagation of lake tsunamis has been studied by numerical wave modeling, only little is known about on- and offshore lacustrine tsunami deposits. In Lake Sils, Switzerland, a large prehistoric mass-movement depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 94 publications
(158 reference statements)
1
23
0
Order By: Relevance
“…Similarly, facies IIIb might be analogous to the organic detritus found in deposits from the Storegga tsunami, termed facies 7 by Bondevik et al (1997a), which also represent material washed into the lake from onshore areas. Facies IIIc (light gray mud capping the sequence) has been attributed to suspension fallout following subaqueous density flows (Mulder and Alexander, 2001), but have also been correlated with seiche effects following tsunami events (e.g., Waldmann et al, 2011;Vasskog et al, 2013;Kempf et al, 2015;Nigg et al, 2021). Based on the above points, we suggest that the facies III successions represent major tsunami events that affected the whole lake basin.…”
Section: Chronological and Sedimentological Interpretationsmentioning
confidence: 72%
“…Similarly, facies IIIb might be analogous to the organic detritus found in deposits from the Storegga tsunami, termed facies 7 by Bondevik et al (1997a), which also represent material washed into the lake from onshore areas. Facies IIIc (light gray mud capping the sequence) has been attributed to suspension fallout following subaqueous density flows (Mulder and Alexander, 2001), but have also been correlated with seiche effects following tsunami events (e.g., Waldmann et al, 2011;Vasskog et al, 2013;Kempf et al, 2015;Nigg et al, 2021). Based on the above points, we suggest that the facies III successions represent major tsunami events that affected the whole lake basin.…”
Section: Chronological and Sedimentological Interpretationsmentioning
confidence: 72%
“…Roberts et al (2013) document sedimentary signatures of the 2007 CE subaerial landslide-generated tsunami in the onshore setting of Lake Chehalis. Nigg, Wohlwend, et al (2021) found sedimentary evidence of a prehistoric tsunami in the shallow-water and coastal area of Lake Sils, Switzerland, that are comparable to marine tsunami deposits.…”
mentioning
confidence: 81%
“…Of the few shallow-water tsunami deposits studied worldwide, several authors have described sharp lower and/or upper sedimentary contacts (Abrantes et al, 2008;Goodman-Tchernov et al, 2009;Sakuna et al, 2012;Smedile et al, 2020;Van den Bergh et al, 2003), as observed at the basal contact of Unit 3. In Lake Sils, Nigg, Wohlwend, et al (2021) observed thick, normally graded sand deposits that were likely formed by the backwash currents of a prehistoric lake tsunami.…”
Section: Unit 3: Normally Graded Sand To Siltmentioning
confidence: 99%
See 2 more Smart Citations